2020
DOI: 10.1590/2177-6709.25.1.020-026.oin
|View full text |Cite
|
Sign up to set email alerts
|

Concrescence: can the teeth involved be moved or separated?

Abstract: The atrophy of the periodontal ligament places the tooth very close to the bone or another tooth, as occurs in unerupted teeth. The absent interdental bone and the lack of functional periodontal stimulus may lead to the fusion of the appositional layers of cement between the roots of the teeth. Concrescence almost always occurs in the region of the maxillary molars. Asymptomatic, it should always be remembered when the proper response to orthodontic movement is not obtained, and there is no apparent explanatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However, Consolaro et al suggested that inflammation caused by trauma or microbial contamination often leads to adhesion of the alveolar bone or root resorption rather than concrescence. 9 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, Consolaro et al suggested that inflammation caused by trauma or microbial contamination often leads to adhesion of the alveolar bone or root resorption rather than concrescence. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the continuously deposited cementum can result in the fusion with the adjacent teeth and even cause bone lesions. However, Consolaro et al suggested that inflammation caused by trauma or microbial contamination often leads to adhesion of the alveolar bone or root resorption rather than concrescence 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations